Performing business and social innovation through accounting inscriptions: An introduction. (May 2018) - Busco, Cristiano; Quattrone, Paolo
Abstract: This introductory essay tries to provide a space for reflecting on the implications of the move from conceiving of accounting as representations to accounting as inscriptions for a critical and interdisciplinary approach to accounting studies. It aims to offer a venue for reflecting on whether there is a positive role that accounting inscriptions play beyond a positivist belief in its representational powers and a constructivist approach that leads to the creation of powerful and dominating institutions such as 'accounting'. We would like to foster a debate on how accounting practices can be re-designed to perform a proactive role in prompting managerial innovation, different forms of empowerment, development of pragmatic management solutions and the mediation of multiple organizational, social and economic interests in the tradition of those accounting studies that expose the emancipatory and enabling effects of accounting practices while maintaining a critical and intellectually solid stance.